The session of the International Institute of Statistics at Mexico, 1933 - Lyon, Stanley (Statistical and Social Inquiry Society of Ireland, 1934)
It is not proposed to give here an account of each paper, but the following summaries of some of the more important papers will give a general idea of their subject matter. The volumes of the Bulletin which will be issued in connection with the Congress at Mexico will contain the papers in full. My purpose is to bring to the notice of the members of this Society briefly the subjects discussed and some of the views expressed thereon.
Read before the Society on 2nd March, 1934
Keywords: International Institute of Statistics; Conference proceedings; 314.15